Park7 interacts with p47(phox) to direct NADPH oxidase-dependent ROS production and protect against sepsis - Liu, Wenjun (Cell Res, 2015)
Inappropriate inflammation responses contribute to mortality during sepsis. Through Toll-like receptors (TLRs), reactive oxygen species (ROS) produced by NADPH oxidase could modulate the inflammation responses. Parkinson disease (autosomal recessive, early onset) 7 (Park7) has a cytoprotective role by eliminating ROS. However, whether Park7 could modulate inflammation responses and mortality in sepsis is unclear. Here, we show that, compared with wild-type mice, Park7(−/−) mice had significantly increased mortality and bacterial burdens in sepsis model along with markedly decreased systemic and local inflammation, and drastically impaired macrophage phagocytosis and bacterial killing abilities. Surprisingly, LPS and phorbol-12-myristate-13-acetate stimulation failed to induce ROS and proinflammatory cytokine production in Park7(−/−) macrophages and Park7-deficient RAW264.7 cells. Through its C-terminus, Park7 binds to p47(phox), a subunit of the NADPH oxidase, to promote NADPH oxidase-dependent production of ROS. Restoration of Park7 expression rescues ROS production and improves survival in LPS-induced sepsis. Together, our study shows that Park7 has a protective role against sepsis by controlling macrophage activation, NADPH oxidase activation and inflammation responses.